Boris Yeltsin: Era Pemerintahan Transisi Pasca Jatuhnya Uni Soviet - Firdaus, Rizal Esya; Supriatna, Nana; Tarunasena, Tarunasena (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2023)
This article is entitled "Boris Yeltsin: Era of Transitional Government Post-Fall of the Soviet Union". This article describes the efforts made by President Boris Yeltsin who was elected as the first Russian president and how his leadership in running the political wheel during the transition period. policy focuses on changing and accustoming society to democratic life. like the implementation of the economic liberalization program with one of them being the granting of privatization vochers. but as is the case with an unstable transition process, the test of democracy must be faced by transitional governments such as the turmoil of regions that want to free themselves and also the readiness of the people to quickly adapt directly to major changes that occur are considered quite difficult given the seventy years of previous government that still made an impression in people's lives. The method used is a historical method which includes heuristic steps, source criticism, interpretation and historiography. The conclusion I got was that the process of democratization programmed by Boris Yeltsin led to the introduction of a top-down model, one of which was reflected in the privatization program that gave rise to the elite or oligarchy as the most prominent group resulting from the democratization. This became a blunder for the second period of Yeltsin's government, the collapse of the ruble, the non-payment of the London Club's foreign debt, and the corruption scandal of the oligarchs (Mabatex) who were in Yeltsin's circle became a bad record in his era of leadership, compounded by his health that was getting worse and worse. get worse. That fact forced him to have to resign as President of Russia on December 31, 1999